Productive performance of seven soybeans genotypes in acid soils of the Colombian Orinoquía - Caicedo-Guerrero, Samuel (2020)
Introduction. In Colombia, soy is one of the main raw materials for the production of feed for animals, demand that was only satisfied in 7% in 2007. In the country, this legume is only produced in the Orinoquía region, as part of the rice-corn-soybean rotation system, and its current commercial production is associated with the Soyica P-34 (Altillanura) and Corpoica Superior 6 (Piedemonte) varieties, which are susceptible to Cercospora sojina, which compromise yield. Objetive. The objective of this work was to identify soy genotypes with specific adaptation for acid soils oxisoles (Altillanura) and inceptisoles (Piedemonte) with superior grain yield a lower affectation by Cercospora sojina K. Hara. Materials and methods. An agronomic evaluation test (PEA) consisting of seven genotypes and two commercial varieties was carried out as controls in six localities located in two sub-regions of the Orinoquía (Altillanura and Piedemonte) during 2011, in a randomized complete block design (DBCA) and four repetitions. The AMMI model and its biplot graph were used to determine the phenotypic stability with the variable grain yield. Results. The AMMI model explained 81.8% of the genotype x locality interaction with the first two main components, the biplot graph allowed to identify three soy genotypes candidates for variety, two with specific adaptation for the Altillanura (L-062 and L-103), and one for Piedemonte (L-189). These genotypes showed higher grain yields by 8% and a lower affectation by Cercospora sojina in relation to commercial witnesses. Conclusion. The study allowed three soy genotypes to be selected and registered as commercial varieties in the National Cultivation System of the ICA as Corpoica Guayuriba (L-189), Corpoica Achagua (L-062) and Corpoica Iraca (L-103), according to their specific adaptation by sub-region.